2015
DOI: 10.1002/aur.1464
|View full text |Cite
|
Sign up to set email alerts
|

Atypical Face Perception in Autism: A Point of View?

Abstract: Face perception is the most commonly used visual metric of social perception in autism. However, when found to be atypical, the origin of face perception differences in autism is contentious. One hypothesis proposes that a locally oriented visual analysis, characteristic of individuals with autism, ultimately affects performance on face tasks where a global analysis is optimal. The objective of this study was to evaluate this hypothesis by assessing face identity discrimination with synthetic faces presented w… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

3
13
1

Year Published

2016
2016
2020
2020

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 13 publications
(17 citation statements)
references
References 71 publications
3
13
1
Order By: Relevance
“…The synthetic face images of the present study were similar to those used by Wilson et al (2002), Habak et al (2008), and Morin et al (2015). A detailed description of these stimuli is provided in Wilson et al (2002).…”
Section: Apparatus and Stimulimentioning
confidence: 99%
See 3 more Smart Citations
“…The synthetic face images of the present study were similar to those used by Wilson et al (2002), Habak et al (2008), and Morin et al (2015). A detailed description of these stimuli is provided in Wilson et al (2002).…”
Section: Apparatus and Stimulimentioning
confidence: 99%
“…Similarly, Wolf et al (2008) asked participants to match facial identities across a 458 change in viewpoint, and reported that children with ASD were significantly less accurate than TD children. In a more recent study from our group, Morin et al (2015) presented target and choice faces in same-view (front, side, inverted) and view-change (front [target], side [choices]) conditions, and asked participants to discriminate between facial identities. Results indicated that adolescents and adults with ASD performed poorer than TD participants only in conditions of viewpoint change, consistent with the findings from previous studies.…”
Section: Introductionmentioning
confidence: 99%
See 2 more Smart Citations
“…Individuals with autism fail to engage in the emotionally or socially relevant content of social scenes by devoting substantially more time to the area of mouth than to eyes 20 . Face identity discrimination in autism is more difficult when access to local cues is minimized, and when dependence on integrative analysis is increased 21 . Other studies demonstrate, however, deficits of ASD individuals in configural face processing (for review, see ref.…”
Section: Introductionmentioning
confidence: 99%